The Computer Boys Take Over: Computers, Programmers, and the Politics of Technical Expertise. - Kane, Carolyn L. (Contemporary Sociology, 2011)
The article reviews the book “The Computer Boys Take Over: Computers, Programmers, and the Politics of Technical Expertise,” by Nathan Ensmenger.